1979
DOI: 10.1136/bmj.1.6159.307
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum and amniotic fluid concentrations of alphafetoprotein in epidermolysis bullosa simplex.

Abstract: proportionating system was dismantled and a gas leak found in the Cambridge Bourdon tube type dialysate temperature gauge which caused the needle pointer to register about 20'C too low. The fault had come on over a period of time and, unfortunately, it had been assumed that the Cambridge

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Although most often associated with open neural tube defects this has been described in association with severe fetal dermatoses 30 33 including EBS. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Although most often associated with open neural tube defects this has been described in association with severe fetal dermatoses 30 33 including EBS. 34 …”
Section: Discussionmentioning
confidence: 99%
“…2 Yacoub et al reported an elevated maternal serum alpha-fetoprotein in three consecutive examinations at 16, 17, and 18 weeks' gestation in an EB pregnancy. 7 These authors proposed that the elevated maternal serum alpha-fetoprotein was the result of fetal serum transudation into a bullae that subsequently ruptured into the amniotic fluid. Our first case further supports Yacoub et al's observation.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this report is the first description of a rare case of EB associated with a normal maternal serum AFP concentration, an unusual manifestation of extracutaneous findings, and no family history of genetic disease. An elevated AFP level in the maternal serum and amniotic fluid has been reported previously in mothers with EB fetuses, resulting from transudation of fetal serum into the amniotic fluid through extensive blistering and denudation of the skin . Although only a few case reports to date have demonstrated a normal AFP concentration in the maternal serum or amniotic fluid in affected pregnancies, the explanation for this normal AFP concentration might be that there had been no leakage of exudate through rupture of bullae at the time of sampling .…”
Section: Discussionmentioning
confidence: 79%